Stalin’s Constitution : Soviet Participatory Politics and the Discussion of the 1936 Draft Constitution - Lomb, Samantha (Taylor & Francis, 2017)
Upon its adoption in December 1936, Soviet leaders hailed the new so-called Stalin Constitution as the most democratic in the world. Scholars have long scoffed at this claim, noting that the mass repression of 1937-1938 that followed rendered it a hollow document. This book focuses on the six-month long popular discussion of the draft Constitution, which preceded its formal adoption in December 1936. Drawing on rich archival sources, this book uses the discussion of the draft 1936 Constitution to examine discourse between the central state leadership and citizens about the new Soviet social contract, which delineated the roles the state and citizens should play in developing socialism